Undrained deformation behavior of saturated soft clay under long-term cyclic loading - Guo, Lin; Wang, Jun; Cai, Yuanqiang; Liu, Hanlong; Gao, Yufeng; Sun, Honglei (Soil dynamics and earthquake engineering (1984), 2013)
Subgrade soils of traffic infrastructures are subjected to large numbers of load applications at a stress level below their shear strength. It is therefore of great practical relevance to study the deformation behavior of soft clay under long-term cyclic loading. In this study, a series of monotonic triaxial tests and long-term cyclic (50,000 cycles) triaxial tests have been carried out to investigate the undrained deformation behavior of undisturbed soft clay from Wenzhou, China. The stress–strain hysteretic loop, resilient modulus and permanent strain of the tested samples were found significantly dependent on CSR and confining pressure. With an increase of CSR and confining pressure, the resilient modulus decreases more significantly with increasing number of cycles and the accumulation rate of permanent strain increases. Furthermore, the shape of the stress–strain hysteretic loop almost remains unchanged and the resilient modulus tends to a steady value after a large number of cycles. Based on the experimental results, two equations are established for the prediction of long-term resilient modulus and permanent strain. Finally, a new critical value of 0.65 is suggested for CSR. When CSR>0.65, the resilient modulus for large number of cycles is reduced to a so called “asymptotic stiffness” and the accumulation rate of permanent strain significantly increases. ► A series of long-term cyclic (50,000 cycles) triaxial tests are carried out. ► Deformation behavior is significantly dependent on CSR and confining pressure. ► After large number of cycles, the resilient modulus tends to be a steady value. ► Two equations are given for long-term resilient modulus and permanent strain. ► A new critical value of 0.65 is suggested for CSR.